Edukasi Literasi Keuangan Syariah sebagai Pendukung Pembangunan Ekonomi Masyarakat di Balai Perkumpulan Sub PPKBD Tambakkemerakan, Krian - Firdaus, Lailul Fuadah (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
This article examines the implementation of a sharia financial literacy education program aimed at supporting community economic development at the Balai Perkumpulan Sub PPKBD Tambakkemerakan, Krian, driven by the persistently low level of community literacy regarding Islamic finance concepts and practices, which has the potential to impede the optimization of Islamic principles-based economic well-being. Employing the Participatory Action Research (PAR) method, this study engaged community members actively throughout the processes of problem identification, program implementation, and evaluation, with activities conducted through socialization sessions, interactive discussions, and practical demonstrations of sharia-compliant financial management in real-life contexts. The findings indicate a measurable improvement in community comprehension of Islamic finance fundamentals, including the prohibition of riba (usury/interest), the importance of financial planning, and the utilization of sharia-compliant financial institutions, alongside observable attitudinal shifts toward more prudent and Islamically normative financial behavior. These outcomes suggest that the program contributes positively to fostering community economic independence and strengthening the application of Islamic economic principles at the household level.